2023
DOI: 10.1002/anie.202302931
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Permeable Dual‐Mechanism‐Driven Graphene Oxide Framework Membranes for Precision Ion Separations

Abstract: Two-dimensional graphene oxide (GO) membranes are gaining popularity as a promising means to address global water scarcity. However, current GO membranes fail to sufficiently exclude angstrom-sized ions from solution. Herein, a de novo "posterior" interfacial polymerization (p-IP) strategy is reported to construct a tailor-made polyamide (PA) network in situ in an ultrathin GO membrane to strengthen size exclusion while imparting a positively charged membrane surface to repel metal ions. The electrostatic repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…When the pH environment is higher than 4.2, the self-standing COF membranes possess negatively charged surfaces and 1D COF channels. Due to the Donnan exclusion between negatively charged dyes and membrane surfaces, the self-standing COF membranes can reject dyes whose dimensions are smaller than COF pores. , Some studies have reported that a membrane is better at rejecting organic micropollutants with the opposite charge to the membrane. However, in those studies, the initial few milliliters of filtrate were generally collected for interception analyses. , Under this circumstance, we believe that the performance of micropollutant removal was due to membrane adsorption rather than interception.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pH environment is higher than 4.2, the self-standing COF membranes possess negatively charged surfaces and 1D COF channels. Due to the Donnan exclusion between negatively charged dyes and membrane surfaces, the self-standing COF membranes can reject dyes whose dimensions are smaller than COF pores. , Some studies have reported that a membrane is better at rejecting organic micropollutants with the opposite charge to the membrane. However, in those studies, the initial few milliliters of filtrate were generally collected for interception analyses. , Under this circumstance, we believe that the performance of micropollutant removal was due to membrane adsorption rather than interception.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the Donnan exclusion between negatively charged dyes and membrane surfaces, the self-standing COF membranes can reject dyes whose dimensions are smaller than COF pores. 44,45 Some studies have reported that a membrane is better at rejecting organic micropollutants with the opposite charge to the membrane. However, in those studies, the initial few milliliters of filtrate were generally collected for interception analyses.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…8−12 The usage of surface-modifying macromolecules, for instance, LSMM (hydrophilic surface-modifying macromolecules) such as poly(4,4-diphenylenemethylene ethylene-urethane)-based compound, 13 silver-containing surface-modifying macromolecules (SMMs) such as diethylene glycol (DEG) and poly(ethylene glycol) (PEG)-based chemistry, 14 and charged surface-modifying macromolecules such as a poly(4,4-diphenyl methylene naphthalene 2,7disulfonate-urethane-based compound, 15,16 for the development of antifouling membranes have been proven to be effective and useful for pharmaceutical and personal care applications. For metal ion separation, positively charged membranes using the new posterior interfacial polymerization (p-IP) technique 17 and nanocomposite sodium alginate hydrogel-coated membranes 18 have been designed. Largescale production of low-cost membranes with tunable structures is key for effective liquid separation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A variety of water treatment technologies have been developed to remove contaminants, such as precipitation, solvent extraction, ion exchange, or electrochemical approaches. Compared to conventional water separation technologies, membrane filtration is considered the most effective method due to its excellent separation efficiency, simple fabrication process, low cost, and broad application. Thus, various filtration membranes for water purification have been addressed in recent research. The usage of surface-modifying macromolecules, for instance, LSMM (hydrophilic surface-modifying macromolecules) such as poly­(4,4-diphenylenemethylene ethylene-urethane)-based compound, silver-containing surface-modifying macromolecules (SMMs) such as diethylene glycol (DEG) and poly­(ethylene glycol) (PEG)-based chemistry, and charged surface-modifying macromolecules such as a poly­(4,4-diphenyl methylene naphthalene 2,7-disulfonate-urethane-based compound, , for the development of antifouling membranes have been proven to be effective and useful for pharmaceutical and personal care applications. For metal ion separation, positively charged membranes using the new posterior interfacial polymerization (p-IP) technique and nanocomposite sodium alginate hydrogel-coated membranes have been designed. Large-scale production of low-cost membranes with tunable structures is key for effective liquid separation. …”
Section: Introductionmentioning
confidence: 99%
“…Utilizing traditional polymer membrane synthesis routes, it is often difficult to precisely regulate the pore structure since the fabrication process involves random cross-linking reactions, , thereby giving rise to broad pore size distribution and low ion selectivity. Advances in nanotechnology have brought intriguing techniques, including top-down and bottom-up synthesis approaches, for creating membranes composed of more defined pore structures. Among them, the porous organic framework is an emerging class of nanomembrane materials, and metal–organic framework (MOF) is one of their representatives. , The structure of MOF materials can be precisely designed and constructed by the precursors, i.e., metal nodes and organic linkers, , and the pore size can be further tuned by chemical modification with specific functional groups . With their narrow pores, MOFs have shown potential for the selective separation of ionic species such as F – /Cl – , Br – /NO 3 – , Na + /K + , and Na + /Ca 2+ , mimicking the transport behavior of biological channels. , This prompts further development of these materials in a variety of ion separation scenarios.…”
Section: Introductionmentioning
confidence: 99%